HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DAN KECEPATAN LARI40 YARDDENGAN HASIL LOMPAT JAUH GAYA JONGKOKSISWA PUTRA KELAS V SDN 010 RAMBAH KAB. ROHUL - Fitri, Danel; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher?s of male students in grade V SDN 010 Rambah while do long jump, research found while student do running start was not optimal. The purpose of this research is to see corelation between explosive power leg muscles and 40 yard running speed with the long jump result squat style of male students class V SDN 010 Rambah Rokan Hulu District. Population in this research is all male students class V SDN 010 Rambah amount 20 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 20 people. Research used standing board jump test be measured with centimeter, 40 yard run test be measured with second and long jump test squat style be measured centimeter. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : 1. Shows that there is correlations of explosive power leg muscle with the long jump result which shows correlation rhitung (0,473)> rtabel (0,456) pada?=0,05. 2 there is correlation of 40 yard running speed with long jump, which shows correlation rhitung (0,616)> rtabel (0,456) pada?=0,05. 3. There is corelations between explosive power leg muscles and 40 yard running speed with the result of long jump, which shows rhitung (0,645)> rtabel (0,456) pada?=0,05Key word : explosive power leg muscles, 40 yard running speed, long jump.